Hubungan Kenaikan Berat Badan Ibu Saat Hamil Dengan Kejadian Berat Badan Bayi Baru Lahir Di Wilayah Kerja Puskesmas Koto Baru Kabupaten Dharmasraya 2023 - Ningsih, Rahayu; Purwati, Rati; Yuliawati, Eni (Akademi Kebidanan Bunga Husada Samarinda, 2023)
Pregnancy can occur due to sexual intercourse or assisted reproductive technology. Pregnancy is known as gravidity or gestation. Weight gain during pregnancy is based on (BMI), ie before pregnancy the woman has a normal BMI (18.5-24.9 kg) so she must gain weight the body weight is around 11.3-15.9 kg, for women who have less BMI (18.5 kg), then they have to increase their weight around 12.7-18 kg while those who have excess weight with BMI 25-29.9 are advised to increase body weight between 6.8-11.3 kg, and if obesity (BMI 30) is recommended between 5-9 kg This study uses an analytical survey method. as many as 27 people (67.5%) and a small number of newborns with low birth weight were 3 people (7.5%), compared to 32 people (80.0%) who had normal newborn weight. The P value obtained is 0.000 - 0.05, which means there is a relationship between the mother's weight gain during pregnancy and the weight of the newborn